1987
DOI: 10.1524/ract.1987.42.3.121
|View full text |Cite
|
Sign up to set email alerts
|

The Basic Chemistry Involved in the Internal-Gelation Method of Precipitating Uranium as Determined by pH Measurements

Abstract: Internal gelation jUranylnitrate IHexamethylenetetramine/Urea / pH /PrecipitationAbstiact Studies were conducted to investigate the chemical reactions thought to be important during hydrolysis and gelatinous precipitation of acid-deficient uranyl nitrate (ADUN) in the internalgelation process for microsphere preparation. Investigations performed to determine pH profiles during urania gelation in conjunction with hexamethylenetetramine (HMTA) decomposition experiments were useful in defining important character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 3 publications
1
65
1
Order By: Relevance
“…An estimated chemical form of metals after gelation is a oxy-hydroxide UO 2 (OH) 2 or hydrated oxide UO 3 xH 2 O [21] . The internal sol-gel method is based on the precipitation of metals, which is governed by a pH shift in the solution towards alkaline.…”
Section: Theory Corrosion Resistancementioning
confidence: 99%
“…An estimated chemical form of metals after gelation is a oxy-hydroxide UO 2 (OH) 2 or hydrated oxide UO 3 xH 2 O [21] . The internal sol-gel method is based on the precipitation of metals, which is governed by a pH shift in the solution towards alkaline.…”
Section: Theory Corrosion Resistancementioning
confidence: 99%
“…This study found the gel spheres could be washed with ammonium hydroxide (NH 4 process. 4 The most important of these reactions are as follows: Urea serves as a complexing agent for the metal (reaction 1).…”
Section: Introductionmentioning
confidence: 99%
“…In this process, chilled clear broth droplets containing the salt of the metal, hexamethylenetetramine (HMTA), and urea are heated, which causes homogenous gelation and solidification of the droplets. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] After washing treatments, the gel spheres can be either air dried for use as engineered ion-exchange materials 7−11 or, depending upon the metal, dried, calcined, and sintered to ceramic microspheres for use as nuclear fuel, 1−6 catalysts, 7−11 getters, 7−10 or dielectrics. [12][13][14] A previously reported test-tube methodology, 15 which was employed to determine the optimum process parameters for preparing hydrous metal oxide microspheres, was also used in this study to determine the optimum process parameters for preparing hydrous aluminum oxide microspheres.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The most important reactions are as follows: Urea serves as a complexing agent for the metal (reaction 1). For broths of certain concentrations, the urea allows stable broths to be prepared at temperatures of 0°C.…”
mentioning
confidence: 99%